Effect of Student Participation in Business Center, Parent's Role, and Self-Efficiency to Entrepreneurship Intention Students of SMK - Andani Apriliana; Ery Tri Djatmika (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this research (1) condition of students’ participation in the business center, parental role, self-efficacy, and student entrepreneur willingness, (2) influence of student participation in the business center, parental role, and self-efficacy partially to student entrepreneur willingness, (3) the influence of participation in the business center, parental role, and self-efficacy on student entrepreneurship willingness, and (4) difference entrepreneur willingness for the first year and second-year students. This study is a comparative causal and technique of collecting data using questionnaire. The result of this research (1) students’ participation in Business Center have high categorized and positively and significantly influence to willingness, (2) parental role is a very high categorical student and have the positive and significant influence to student entrepreneurship willingness, (3) self-efficacy of the high categorized student, but not positively and significantly influence to intent entrepreneurship, (4) willingness of entrepreneurship is very high categorize, (5) students’ participation in Business Center and parental role simultaneously has positively and significantly influence on willingness, (6) there is a difference of willingness of student entrepreneur for the first year students with second year students, (7) there is no difference in student participation in Business Center for the first year and second year students, (8) there is a difference of parental role of first year and second year students, and (9) there no difference of self-efficacy for the first year with second year students.